Eliminasi Kandungan Timbal (Pb) Pada Air Laut Tercemar di Kota Kendari Menggunakan Kulit Pisang Kepok - Adami, Aryani; Karim, Karim; Rosdiana, Rosdiana (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
Heavy metal pollution, particularly lead (Pb), in the waters of Kendari Bay has become a serious environmental problem due to its toxic and bioaccumulative nature. This study aims to analyze the effectiveness of a bioadsorbent derived from banana peel waste in reducing Pb levels in seawater samples from Kendari Bay. The bioadsorbent was prepared through carbonization to remove moisture content and increase the surface area of the adsorbent. The adsorption process was carried out by mixing 60 grams of banana peel charcoal with 500 mL of seawater samples and allowing it to stand at three different contact times: 60 minutes, 90 minutes, and 120 minutes. Pb concentrations before and after treatment were analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that banana peel exhibited maximum adsorption capacity at a contact time of 120 minutes, with an effectiveness value of 64.95%. Banana peel charcoal contains cellulose with hydroxyl functional groups  (-OH) that act as active sites for binding Pb ions. The longer contact time between adsorbent and adsorbate increases the amount of Pb ions adsorbed onto the surface until equilibrium is reached. Therefore, banana peel bioadsorbent has strong potential as an economical, environmentally friendly, and effective adsorbent for reducing lead levels in seawater from Kendari Bay. For future research, it is necessary to develop bioadsorbent activation methods, physical and chemical, in order to increase the surface area and the number of active sites, thereby enhancing the adsorption capacity for heavy metals.